Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:1. The role of institutional change in improving the quality of health services: An applied study At the Civil Hospital in Khamis MushaitMr. Ayidh Hamoud Alshahrani, Mr. Abdullah Mohammed Alshehri, Mr. Saad Awad Alqahtani2. Strategies for solving administrative problems using machine learning technology on AmazonMs. Rana Mohammed Alsuhaimi, Ms. Shomoukh Abdullah Aldhafeeri, Ms. Maha Mohammed Alotaibi, Dr. Futoon Ahmed Othman3. Accounting Environment Readiness for The Application of International Financial Reporting Standards (IFRS) in KSA: An analysis Study (2016 - 2017)Asst-Prof. Shihabeldeen Mohamed Ahmed ,Asst-Prof. Abu Baker Ahmed Yousif4. The Role of the Knowledge Economy in Developing the Export Sector in the Kingdom of Saudi Arabia During Period (2000-2021)Co-Prof. Sahar Hassan Khayat ,Ms. Ghadah Muhammed AlAmri5. International legal mechanisms to protect the environment from climate changeMr. Abdulmajeed Motib Alotaebi6. The crime of human trafficking (A comparative legal study between Egypt and Saudi Arabia)Dr. Reem Gomaa Zekry7. Legal regulations to ensure the satisfaction of living organ donorsMr. "Mohammad Ali" Jehad Sarah8. The relationship between accreditation standards and organizational excellence and their role in the excellence of administrative leadershipDr. Norah Abdulaziz Ibrahim Alsaleem
Keywords: Journal of Economic, Administrative and Legal Sciences